(untitled) (International Journal of Engineering and Computer Science, 2017)
Image enhancement is one of the important technique in image processing field. The main objective of this technique is to improve the quality and information of the image and to provide better visualization to the image. In this paper we have used two techniques to enhance the quality of an image. These two are histogram and fuzzy logic. Histogram and fuzzy techniques can be used to enhance the quality of image. Fuzzy logic can be used to interpret human knowledge in the form of fuzzy if-then rules. Histogram technique is usually used to increase the contrast of an image. This paper presents the review of different histogram and fuzzy techniques used.